2015
DOI: 10.1186/s12889-015-2293-1
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the AFLY5 RCT process evaluation: implications for the design of physical activity and nutrition interventions in schools

Abstract: BackgroundSystematic reviews have highlighted that school-based diet and physical activity (PA) interventions have had limited effects. This study used qualitative methods to examine how the effectiveness of future primary (elementary) school diet and PA interventions could be improved.MethodsData are from the Active For Life Year 5 (AFLY5) study, which was a cluster randomised trial conducted in 60 UK primary schools. Year 5 (8–9 years of age) pupils in the 30 intervention schools received a 12-month interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 30 publications
1
52
0
1
Order By: Relevance
“…Výzkumy se zaměřují i na některá dílčí témata. Několik výzkumů zkoumalo výsledky zavádění praktik, které měly za cíl zlepšit zdraví dětí ve školách (Gill, Chestnutt, & Channing, 2009;Gugglberger, Flaschberger, & Teutsch, 2017;Christian et al, 2015;Standage, Cumming, & Gillison, 2013;Storey et al, 2016); jiné výzkumy jsou zaměřeny na zlepšení stravovacích návyků (Jago et al, 2015;Moore, Murphy, Tapper, & Moore, 2010) nebo prevenci obezity u dětí (Howard-Drake & Halliday, 2016). Součástí života některých mladých studentů jsou drogy a alkohol, ředitelé k tomuto tématu zastávají určitá stanoviska, realizují konkrétní preventivní opatření a řeší vzniklé incidenty.…”
Section: Výsledky Rešeršeunclassified
“…Výzkumy se zaměřují i na některá dílčí témata. Několik výzkumů zkoumalo výsledky zavádění praktik, které měly za cíl zlepšit zdraví dětí ve školách (Gill, Chestnutt, & Channing, 2009;Gugglberger, Flaschberger, & Teutsch, 2017;Christian et al, 2015;Standage, Cumming, & Gillison, 2013;Storey et al, 2016); jiné výzkumy jsou zaměřeny na zlepšení stravovacích návyků (Jago et al, 2015;Moore, Murphy, Tapper, & Moore, 2010) nebo prevenci obezity u dětí (Howard-Drake & Halliday, 2016). Součástí života některých mladých studentů jsou drogy a alkohol, ředitelé k tomuto tématu zastávají určitá stanoviska, realizují konkrétní preventivní opatření a řeší vzniklé incidenty.…”
Section: Výsledky Rešeršeunclassified
“…Moreover, a process evaluation collects data about programme delivery, receipt and setting which are essential to understanding the social processes that influence why a complex intervention does or does not have its intended impact 3234 For this reason, process evaluations are increasingly reported in conjunction with RCT outcomes to explain impact and understand implications for future use of the intervention 35–38. Therefore, identifying how, for whom and in what contexts this type of intervention works will contribute new knowledge about the implementation of multicomponent, consumer-focussed eHealth interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that future interventions need to be more intensive and embed diet and physical activity behaviour change across the curriculum. In addition, interventions should aim to increase knowledge, motivation and skills of the children involved, find ways to increase child engagement in programme content and, crucially, engage parents [16]. Based on the lessons learnt from previous school-based interventions, we developed the Healthy Lifestyles Programme; a school-based obesity prevention intervention.…”
Section: Introductionmentioning
confidence: 99%